Older veterans associated with reduced risk of cancer: Retrospective nationwide matched cohort study in Taiwan - Pan, Li-Fei; Chang, Renin; Hsu, Chung Y.; Tsui, Kuan-Hao (Frontiers in Medicine, 2023)
IMPORTANCE: It remains unknown whether Taiwanese veterans have a lower risk of subsequent cancer compared to non-veterans. OBJECTIVE: To examine whether veterans are associated with reduced cancer risk. METHODS: From January 2004 to December 2017, this study included 957 veterans and 957 civilians who were propensity-score (PS) matched by years of birth, sex, residence, index year, days in the hospital, frequency of outpatient visits, and relevant comorbidities at baseline. Multivariate Cox proportional hazards regression analysis was applied to compare the risks of cancer, overall and by subgroup, and mortality. The participants were all cancers free at the baseline. EXPOSURES: Veterans retrieved from Taiwan National Health Insurance Research Database (NHIRD). MAIN OUTOME: Cancer extracted from the Registry for Catastrophic Illness Patients Database (RCIPD). RESULTS: Overall, 1 914 participants were included, and 957 veterans with mean [SD] age 75.9 (6.79) years, 946 men (98.9%). The mean follow-up was about 10.5 (±4.51) years. Cancer was recorded 6.68% (N= 64) and 12.12% (N= 116) in veterans and non-veterans respectively. Veterans were associated with decreased risk (adjusted hazard ratio (aHR), 0.57; 95% CI, 0.41-0.78; P < .001) of cancer compared with civilians after controlling for age, sex, urbanization, hypertension, diabetes, hyperlipidemia, cardiovascular event, COPD, asthma, chronic liver disease, alcohol related illness, and Parkinson disease. Cancer-subgroup analyses verified this finding (HRs <1.0). Decreased incidence rate was predominantly for liver cancer (aHR, 0.18; 95% CI, 0.05-0.72; P < 0.05). Conclusions: Taiwanese older veterans are associated with reduced overall cancer risk than individuals without veteran status.